1978
DOI: 10.1007/bf00381643
|View full text |Cite
|
Sign up to set email alerts
|

Komplikationen der Arthroskopie

Abstract: This review is drawn from a total of 3,714 knee arthroscopies carried out on patients from six clinics. The diagnostic value of arthroscopy at this site is established for it can improve prognostication, prevention and treatment of derangements of the knee. The complications of the procedure, both theoretical and in practice, have been considered by subdividing them into four groups. Firstly, the infection rate following arthroscopy alone was nil. Secondly, minor articular cartilage damage attributable to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…In agreement with other authors (Jackson & Abe 1972, Gillquist et al 1977, Dick et al 1978 we found no complications caused by the arthroscopic instrumentation. The diagnostic accuracy has not, to our knowledge, been previously evaluated by means of the diagnostic specificity and sensitivity, which is the clinically most relevant method to evaluate a diaenostic test WecNumbers in brackets show the number of diagnoses missed at initial arthroscopy.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other authors (Jackson & Abe 1972, Gillquist et al 1977, Dick et al 1978 we found no complications caused by the arthroscopic instrumentation. The diagnostic accuracy has not, to our knowledge, been previously evaluated by means of the diagnostic specificity and sensitivity, which is the clinically most relevant method to evaluate a diaenostic test WecNumbers in brackets show the number of diagnoses missed at initial arthroscopy.…”
Section: Discussionsupporting
confidence: 93%
“…The possible untoward sequelae to arthroscopic surgery include infection, iatrogenic damage to the articular cartilage, introduction of foreign material (including breaking of an instrument within the joint) and haemarthrosis (Dick et al 1978). Haemorrhage associated with cannulation or biopsy is minimal and insignificant.…”
Section: Problems and Complicationsmentioning
confidence: 99%
“…The overall complication rate of arthroscopy is reported to be over 8% [12]. This includes the breakage of biopsy forceps and knife blades [4,6], plastic draping in the joint Correspondence to: M. Sadat-Ali [7], and neural and vascular injuries [2,8,11]. Fire mishaps initiated by the light source could be another complication during routine arthroscopy if appropriate care is not taken.…”
Section: Discussionmentioning
confidence: 99%